Infectious gastroenteritis and the need for strict contact precaution procedures in adults presenting to the emergency department: a Danish register-based study. Issue 4 (April 2018) - Skyum, F.; Andersen, V.; Chen, M.; Pedersen, C.; Mogensen, C.B.
Summary: Background: Acute infectious gastroenteritis requires contact precautions to prevent spread. On acute admission, the cause of diarrhoea is unknown, so the decision regarding which patients to isolate has to be made on clinical information with a risk of inexpedient use of contact precautions. Aim: To investigate how often gastroenteritis occurs (and therefore how often the need for isolation has to be assessed) in Danish emergency departments, and how often patients have to remain on contact precautions according to the results of faecal samples. Methods: This Danish register-based retrospective cohort study on adults in Danish emergency departments used three data sources: discharge diagnoses from the Danish National Patient Register; microbiological results from faecal samples provided in the emergency department; and the causes of hospital admission based on the chief complaint. Findings: Among 66, 885 acute admissions, 4.3% of patients had at least one feature of gastroenteritis: admission with diarrhoea as the chief complaint (1.6%); microbiological examination of faecal sample (2.8%); and discharged with a diagnosis of gastroenteritis (1.7%). Nineteen percent of those who had a faecal sample tested were found to have norovirus or Clostridium difficile, and needed to remain on strict contact precautions. Conclusion: The initiation of contact precautions has to be assessed for 4.3% of all emergency department patients; 19% of the patients who had a faecal sample tested had highly contagious gastroenteritis and required strict contact precautions. Further studies are needed to develop tools to determine which patients to isolate.